Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Qwerty90

  • 3 years ago

Gina and Sean wrote the following proofs. Gina’s Proof: Step 1: Area of PQRS = (a + b) 2 = a2 + b2 + 4ab Step 2: Area of 4 triangles = 4ab Step 3: Area of KLMN = c2 = area of PQRS – area of 4 triangles = a2 + b2 + 4ab – 4ab Hence, c2 = a2 + b2 Sean’s Proof: Step 1: Area of triangle EAF = ab; hence the area of 4 triangles = 4ab Step 2: Area of square ABCD = (a – b) 2 = a2 + b2 – 4ab Step 3: Area of EFGH = c2 = Area of 4 triangles + area of ABCD = 4ab + a2 + b2 – 4ab Hence c2 = a2 + b2 Which statement gives the correct conclusion about the proof

  • This Question is Open
  1. Qwerty90
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    1 Attachment
  2. goldh31
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    shouldn't this be in math?

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy